The Benefits Of Variation Style Teaching Method Using Simulation In Learning I Ps In Class V I Sd Negeri 03 Padang District Of Lengayang Marapalam Academic Year 2015/2016 - Elianis Elianis (Fakultas Sastra Universitas Ekasakti, 2017)
Based on direct observation and assessment, that IPS education is one of the subjects in elementary school that for some students feels boring, less attractive and tend to monotone. IPS education is a very strict subject and in the form of hapalan-hapalan and the scope of the learning is human as a member of society, the symptoms and social problems and events about human life in society. Therefore, students are required to have more full and serious interest to study it In the evaluation, the teaching of social studies for students of SDN 03 Padang District of Lengayang Marapalam Academic Year 2015/2016 industrious and keen to learn, they will be easier to work on and solve the problems it faces, and they will be fond of social studies for social studies is not an exact lesson or an exact science that requires a definite answer. This study is an action research (PTK) using the model Kemmis and MC. Taggart (1988). Which Kemmis developed a model based on a system of self-reflection spiral starts with a plan, action, observation and reflection, for re-planning is the basis for a square - square troubleshooting . Student achievement SD Negeri 03 Padang District of Lengayang Marapalam Academic Year 2015/2016 class VI is still not satisfactory. This paper has the objective to define and clarify the application of multimedia-based learning media as an attempt to improve learning achievement IPS in SD Negeri 03 Padang Marapalam District of Lengayang in academic year 2015/2016 . This research is a class action ( classroom action research ). In the initial condition (prasiklus) achievement of sixth grade social studies on the competence of the formation of market prices are still low. Of the 27 students who score less than KKM 14 students (53.57%), within the limits of KKM there are 7 students (25%) and exceeded the limits of existing KKM 6 students (21, 43%) with an average grade 66.75.After the action (action) in the first cycle of learning achievement IPS started to increase. The final evaluation of results obtained by the average - average grade 75, 82 with a highest score of 90, the lowest score of 65. Of the 27 students who value under KKM there are 7 students (25%), well above the KKM there are 20 students (71.43%), limit KKM completed there is 1 student (3.57%). Because not meet the minimum of 85% of pupils achieve completeness criteria of at least 72 (seventy-two) it is necessary to follow up with the second cycle. In the second cycle of evaluation results obtained at the end of the lesson learned by the average - average grade 82.11 with a highest score of 100 with the lowest value of 68. This indicates the second cycle of the sixth grade social studies achievement is very satisfactory. During the learning takes place by using multimedia-based learning media,teaching material that students absorb more deeply and fully, in addition, the learning process becomes more interactive, vivid and interesting. Therefore, interactive multimedia-based learning media can be used as an alternative medium of learning to apply in Social Science subjects in schools at both the elementary to university.